2020
DOI: 10.1038/s41598-020-74097-7
|View full text |Cite
|
Sign up to set email alerts
|

Adding carbon fiber to shoe soles may not improve running economy: a muscle-level explanation

Abstract: In an attempt to improve their distance-running performance, many athletes race with carbon fiber plates embedded in their shoe soles. Accordingly, we sought to establish whether, and if so how, adding carbon fiber plates to shoes soles reduces athlete aerobic energy expenditure during running (improves running economy). We tested 15 athletes as they ran at 3.5 m/s in four footwear conditions that varied in shoe sole bending stiffness, modified by carbon fiber plates. For each condition, we quantified athlete … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 64 publications
1
38
0
Order By: Relevance
“…Conversely, cutting the carbon-fiber plate only resulted in a non-significant 0.5% difference from the intact shoe. As such, our findings are in line with the data of the vast majority of studies that evaluated the effects of LBS with flat plates/insoles [14][15][16][17] . When directly comparing footwear conditions at the group level, without focusing on individual responders or the individual stiffness condition with the lowest metabolic rate, only Roy and Stefanyshyn 12 and Oh and Park 18 showed improvements in running economy (0.8 and 1.1%, respectively).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Conversely, cutting the carbon-fiber plate only resulted in a non-significant 0.5% difference from the intact shoe. As such, our findings are in line with the data of the vast majority of studies that evaluated the effects of LBS with flat plates/insoles [14][15][16][17] . When directly comparing footwear conditions at the group level, without focusing on individual responders or the individual stiffness condition with the lowest metabolic rate, only Roy and Stefanyshyn 12 and Oh and Park 18 showed improvements in running economy (0.8 and 1.1%, respectively).…”
Section: Discussionsupporting
confidence: 90%
“…In 2006, Roy and Stefanyshyn 12 showed small (1%) improvements in running economy with increased LBS. However, since then, reported effects of LBS on running economy have been mixed, with studies finding deteriorations 14 , no effect [15][16][17] , or small (~1%) 12,18 , to large improvements (3-4%) 1,7,8,19 (for review see 20 ). Importantly, the largest improvements in running economy have been reported in studies assessing VF shoes 1,7,8 , suggesting that the geometry and stiffness of the curved VF plate may provide additional savings compared to flat plates previously tested.…”
Section: Introductionmentioning
confidence: 99%
“…A recently published study investigated how running in footwear with differently stiff carbon fiber plates can affect the soleus muscle fascicle dynamics and running economy. 40 The authors did not find any differences in soleus fascicle pennation, force, length, velocity, or stride-average soleus active muscle volume due to altered MBS during running. Beck et al 40 therefore concluded that inserting carbon fiber plates in shoes may not improve running economy.…”
Section: Discussionmentioning
confidence: 77%
“…Data is conflicting about whether a carbon fiber plate improves running performance and if so, by what means (Roy and Stefanyshyn, 2006 ; Willwacher et al, 2014 ; Madden et al, 2016 ; Flores et al, 2019 ; Beck et al, 2020 ; Healey and Hoogkamer, 2020 ; Cigoja et al, 2021 ). Carbon fiber plates increase the longitudinal bending stiffness of the shoe, which has been found to reduce negative work at the metatarsophalangeal joint and alter the ground reaction force moment arm in a way that reduces oxygen consumption (Roy and Stefanyshyn, 2006 ; Willwacher et al, 2013 , 2014 ; Stefanyshyn and Wannop, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Increasing midsole bending stiffness is typically associated with performance improvement (e.g., faster running speed) (Nigg et al, 2020 ). However, the benefit of adding a carbon fiber plate to increase midsole bending stiffness and the important characteristics of the plate, including its shape, remain under debate (Beck et al, 2020 ; Healey and Hoogkamer, 2020 ).…”
Section: Footwear Constructionmentioning
confidence: 99%